Pharmacist Rethink through a Planetary Health Lens - Sandeep Maharaj DBA; Mala Moonilal BSc; Satish Jankie PhD; Darren Dookeram DM (SAGE Publishing, 2021)
Planetary Health is a rapidly developing field that is gaining momentum and significance as the world grapples with the devastating effects of infectious diseases, climate change, biodiversity loss, complex food insecurities, and international competition for resources. These challenges are often attributable to the financial activity made by nation states and increasing disposable individual wealth. The outcomes have created a perfect storm of events that, if not managed properly, threatens the health of current and future generations. Given the front-line role pharmacists play within health system in the community and institutional levels, the profession is uniquely positioned to make a meaningful impact to planetary health. This article aims to explore contributions pharmacists can make to secure planetary health.